2013
DOI: 10.1136/bjophthalmol-2013-303343
|View full text |Cite
|
Sign up to set email alerts
|

In vivo high-frequency contrast-enhanced ultrasonography of choroidal melanoma in rabbits: imaging features and histopathologic correlations

Abstract: Purpose To evaluate the utility of in vivo imaging of rabbit model of choroidal melanoma utilizing high-frequency contrast-enhanced ultrasound (HF-CE-US) with 2-or 3-dimensional modes, and to correlate the sonographic findings with histopathologic characteristics. Methods Five New Zealand white rabbits which were immunosuppressed with daily cyclosporin A were inoculated into their right eyes with aliquots of 1.5×106 / 50 µL of 92.1 human uveal melanoma cells cultured in RPMI. At week 4, the tumor-bearing eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
(32 reference statements)
0
13
0
1
Order By: Relevance
“…20,21 Previous studies showing success of SF6 microbubble enhancement of the microvasculature in the eyes of small animals such as rabbits and mice, combined with the results shown here of successful enhancement of the pecten oculi in several avian species, are encouraging when considering the small eyes and delicate microvasculature of many avian species. 37,42 Enhanced visualization of the pecten oculi and its vasculature using a readily available diagnostic imaging method such as CE-US would facilitate future studies evaluating the role of the pecten oculi in posterior segment diseases, including retinal degenerations, such as rdd, rge, and beg. [43][44][45][46] In the future, CE-US could be employed in the diagnosis of pecten oculi abnormalities as well as in the monitoring of progression vs. healing in pathological processes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…20,21 Previous studies showing success of SF6 microbubble enhancement of the microvasculature in the eyes of small animals such as rabbits and mice, combined with the results shown here of successful enhancement of the pecten oculi in several avian species, are encouraging when considering the small eyes and delicate microvasculature of many avian species. 37,42 Enhanced visualization of the pecten oculi and its vasculature using a readily available diagnostic imaging method such as CE-US would facilitate future studies evaluating the role of the pecten oculi in posterior segment diseases, including retinal degenerations, such as rdd, rge, and beg. [43][44][45][46] In the future, CE-US could be employed in the diagnosis of pecten oculi abnormalities as well as in the monitoring of progression vs. healing in pathological processes.…”
Section: Resultsmentioning
confidence: 99%
“…For example, one study showed a correlation between CE‐US and histologic results of assessing microvascular density and blood volume in murine uveal melanomas, which suggests that CE‐US is a reliable examination modality for evaluation of intraocular tumors even in small species . Similar results were shown more recently in a study evaluating CE‐US and histologic characteristics of choroidal melanomas in rabbits . Monitoring the vascular status of the pecten oculi is also important for primary or other secondary retinal diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tolerability of CEUS was unknown until Seiler et al 7 examined equine soft tissue structures of the distal limb by intravenous and regional intra-arterial perfluorobutane. In experimental ophthalmology, CEUS visualized normal vs impaired choroidal perfusion, 15 and correlated with histologic size and vascularity of uveal melanomas in rabbits 16 and mice. 17 The characterization of perfusional features of intraocular masses such as melanoma, hemangiosarcoma, 18 medulloepithelioma/retinoblastoma, 19 or lymphoma might be a future CEUS indication in horses.…”
mentioning
confidence: 97%
“…In a study on circulating malignant cells, all of the 17 rabbits that were available for testing had metastases in the lungs [49], and 18% developed liver micrometastases. Subsequently, several experiments were undertaken based on the same rabbit model [50,51,52,53]. …”
Section: Rabbit Modelmentioning
confidence: 99%